Combining Intergenerational and International Justice - Christoph Lumer (Intergenerational Justice Review)
Intergenerational justice not only requires the adoption of best practices and policies, but also the prevention and repression of deleterious and morally blameworthy human behaviour which have severe impacts on the long-term health, safety and means of survival of groups of individuals. While many international crimes have indirect consequences on the well-being of present and future generations, it cannot be said that existing international criminal law is currently well-placed to directly and clearly protect intergenerational rights. As such, the development of a new type of international crime, crimes against future generations, may be a promising avenue for implementing intergenerational justice. Such a crime would penalise acts or conduct that amount to serious violations of existing international law regarding economic, social and cultural rights or the environment.